Lost in the Mist: Acute Adrenal Crisis Following Intranasal Fluticasone Propionate Overuse - Arturo Loaiza-Bonilla; Tollin Sullivan; Ryan Kendall Harris (Case Reports in Medicine)
Introduction. Acute adrenal crisis in relation to nasal steroid overuse has been reported very scantly in English medical literature and remains an underdiagnosed condition. Case presentation. A 55 year-old male presented with altered mental status, retrograde amnesia, fluid refractory hypotension, abdominal pain, fever, and chest pain. Physical examination revealed amnesia, bradypsychia, tachycardia, decreased muscle tone and hyporeflexia. Overuse of nasal steroid was suspected by history. Random early morning cortisol level was < 0.2 mcg/dL. The patient was started on hydrocortisone and within 24 hours he had a full recovery. Conclusion. This one-of-a-kind case describes acute adrenal crisis secondary to withdrawal from inhaled nasal corticosteroids overuse in a patient with particular risk factors. Prevention and early recognition of this disorder can significantly reduce its morbidity and mortality.